Healthcare resource use and costs reduction with aripiprazole once-monthly in schizophrenia: AMBITION, a real-world study - Sanchez-Gistau, Vanessa; Moreno, María José; Gómez-Lus, Susana; Sicras-Mainar, Antoni; Crespo-Facorro, Benedicto (Frontiers in Psychiatry, 2023)
Objective This study aims to compare the hospitalization rate in individuals with schizophrenia who started their treatment with aripiprazole once monthly (AOM400) or atypical oral antipsychotics (OA) in Spain. Methods This is an observational and retrospective study based on the electronic medical records from the BIG-PAC database. The study population consisted of individuals diagnosed with schizophrenia who initiated their treatment with AOM400 (AOM cohort) or atypical OA (OA cohort) from 01/01/2017 to 31/12/2019. A 1:1 propensity score matching (PSM) procedure was conducted to match individuals of both cohorts. The number and duration of hospitalizations, persistence to treatment, healthcare resources use, and costs were analyzed after 12 months. Results After the PSM, 1,017 individuals were included in each cohort [age: 41.4 years (SD: 10.6); males: 54.6%]. During the follow-up period, the AOM cohort had a 40% lower risk of hospitalization than the OA group [HR: 0.60 (95% confidence interval, CI: 0.49–0.74)]. The median time to the first hospitalization was longer in individuals with AOM400 compared to those with OA (197 days compared to 174 days; p < 0.004), whereas hospital admissions were shorter (AOM400: 6 compared to OA: 11 days; p < 0.001). After 12 months, individuals receiving AOM400 were more persistent than those with OA (64.9% compared to 53.7%; p < 0.001). The OA cohort required more healthcare resources, mainly visits to primary care physicians, specialists, and emergency rooms than those receiving AOM400 (p ≤ 0.005 in all comparisons). AOM400 reduced the costs of hospitalizations, and emergency room, specialist and primary care visits by 50.4, 36.7, 16.1, and 10.9%, respectively, in comparison to the treatment with atypical OA. AOM400 led to annual cost savings of €1,717.9 per individual, from the societal perspective. Conclusion Aripiprazole once monthly reduces the number and duration of hospitalizations, together with the treatment costs of schizophrenia, as it reduces the use of healthcare resources and productivity losses in these individuals.